Analysis of the Influence of Economic Growth, Education Level, Unemployment and Poverty on the Human Development Index in East Java Province - Efendi, Bagus Arya Nur; Marseto, Marseto; Utami, Anisa Fitria (Indonesian Journal Publisher, 2025)
This study was conducted to analyze the influence of economic growth, education level, unemployment, and poverty on the Human Development Index (HDI) in East Java Province for the period 2013-2022. This study used quantitative methods with secondary data from the Central Statistics Agency (BPS). The analysis was conducted through multiple linear regression with the classical assumption test, F-test, and t-test to determine the simultaneous and partial effects between variables. The results showed that economic growth and the unemployment rate did not significantly influence the HDI. Conversely, education level had a significant positive effect on the HDI, while poverty had a significant negative effect. These findings confirm that improving the quality of education and reducing poverty levels are key factors in improving human development in East Java.